The Role of Public Participation for Determining Sustainability Indicators for Arctic Tourism - Rannveig Ólafsdóttir (Sustainability, 2020)
The new paradigm of sustainable development highlights the importance of enforcing defined boundaries between economies, societies, and the environment within a system. Sustainability indicators are tools that have proven to be a successful aid in defining and creating system boundaries. This paper focuses on the development of sustainability indicators for Arctic tourism, with a special emphasis on the role of public participation in their determination. It presents a stakeholder-centric approach to indicator selection by developing a framework that effectively integrates public participation in the processes of indicators’ selection and designation, and highlights the importance of combining local and expert knowledge in these processes. The results reveal that the making of sustainability indicators is an ideal platform for local voices to be heard, and thus to have a significant stake in the overall process of tourism development. The most effective way to make their voices heard in the final decision-making process is via their evaluation of the adaptability and prioritization of these indicators. The results, furthermore, stress that sustainability indicators need to be constantly re-evaluated and updated, as tourism is part of a complex and dynamic system that is constantly changing. To provide a holistic vision of the impact of economic, environmental, and social factors, as well as the causality between them in the system, sustainability indicators must be integrated from many indicators. Since the monitoring of conventional indicators is often less complicated and more cost-effective than the monitoring of integrated indicators, a better result can however be reached by combining conventional indicators with sustainability indicators.